Study of optoelectronic and thermoelectric properties of double perovskites for renewable energy. (4th October 2021) - AL-Anazy, Murefah Mana; Ali, Malak Azmat; Bouzgarrou, S; Murtaza, G; Al-Muhimeed, Tahani I; AlObaid, Abeer A; Mera, Abeer; Mahmood, Q; Nazir, Ghazanfar
Abstract: It is compulsory to develop technologies able to generate energy at negligible cost to the environment. Therefore, in present work, lead free vacancy ordered double perovskites M2 TeBr6 (M = Rb, Cs) were reported as green energy materials on basis of full potential linearized augmented plane wave method calculations. The study has been carried out in terms of structural, mechanical, electronic, optical, and thermoelectric properties. It was noted from values of tolerance factor and formation energy that both the M2 TeBr6 compounds are stable in perovskite structure. The band gaps were calculated as indirect of values 2.09 eV for Rb2 TeBr6 and 2.10 eV for Cs2 TeBr6 with EV-GGA. These gaps were found in close resemblance with experimental results. The optical properties such as real and imaginary parts of dielectric function, optical conductivity and reflectivity calculated via EV-GGA ensured the use of both the M2 TeBr6 compounds for optoelectronic devices and solar cell applications. Also, the reasonable values of Seebeck coefficients and figure of merit suggested the studied compounds for thermoelectric power generation.